2018
DOI: 10.22214/ijraset.2018.5115
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Bending Strength of Aluminium Silicon Carbide Metal Matrix Composite Spur Gear by Increasing Fillet Radius

Abstract: In this paper bending strength of spur gear teeth improved by increasing the fillet radius at root of the teeth. Spur gear geometry prepared using SolidWorks and imported in Ansys to analyse the stress and strain under specific loading condition. The fillet radius at root of teeth was increased from 0.15mm to 0.75mm with an increment of 0.15mm each time. With the increase in fillet radius of gear teeth, decrement of Von-mises stress, Von-mises strain and deformation of spur gear tooth is achieved indicating th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…The influence of gear radii has only been investigated regarding the load carrying capacity of polymer gears, but not on wear. It has been shown that increased radii reduce stresses in the tooth root and increase the load carrying capacity [17].…”
Section: Introductionmentioning
confidence: 99%
“…The influence of gear radii has only been investigated regarding the load carrying capacity of polymer gears, but not on wear. It has been shown that increased radii reduce stresses in the tooth root and increase the load carrying capacity [17].…”
Section: Introductionmentioning
confidence: 99%